The NextGen Study: patient motivation for participation in genome sequencing for carrier status. Issue 5 (2nd July 2017) - Kauffman, Tia L.; Irving, Stephanie A.; Leo, Michael C.; Gilmore, Marian J.; Himes, Patricia; McMullen, Carmit K.; Morris, Elissa; Schneider, Jennifer; Wilfond, Benjamin S.; Goddard, Katrina A. B.
Abstract: Background: While translational genomic sequencing research is increasing, few studies have been limited to healthy individuals; most have focused on patients with a disease or a strong family history of a disorder. The limited studies that have included healthy individuals have focused on the disclosure of medically actionable secondary results, rather than carrier status, to assess reproductive risks. To address this important gap, we conducted the NextGen study, which focuses on carrier status and medically actionable secondary findings in a population of women planning a pregnancy. Methods: We assessed 310 participants' motivations for receiving genome sequencing for expanded carrier screening and experiences with familial genetic conditions that may relate to study participation. Results: Most participants reported that obtaining general health information from genome sequencing was their primary motivator, even though they were recruited to join a study to learn more about carrier status. Forty‐two percent of enrolled women became pregnant prior to obtaining sequencing results. Conclusion: Genomic carrier testing may need to be offered to women prior to active pregnancy efforts to be useful for reproductive planning. Abstract : Most preconception women reported that obtaining general health information from genome sequencing was their primary motivator for being in the study, even though they were recruited to join a study to learn more about carrier status. Forty‐two percent of enrolled women became pregnant prior to obtaining sequencing results. Genomic carrier testing may need to be offered to women prior to active pregnancy efforts to be useful for reproductive planning.